Konstribusi Ilmuwan Indonesia dalam Pengembangan Matakuliah ‘Ulumul Qur’an di Perguruan Tinggi 2010-2023 - Ulya, Wardatul; Masri, Dedi; Alfiansyah, Muhammad (Ikatan Da'i Indonesia, 2023)
This newsletter examines numerous works of 'Ulûm Al-Qur'ân written through Indonesian scientists which might be used and widely used as references in universities and their actual contributions; due to the fact thus far what has been used as a reference is the paintings of 'Ulûm Al-Qur'ân in Arabic or a number of its translations. This studies became conducted in the form of qualitative studies the usage of the library research method with statistics series strategies inside the form of documentation of the literature with the aid of 'Ulûm Al-Qur'ân to then perform a descriptive-interpretative analysis. From the studies in preferred it became concluded that inside the 2010-present duration the works of 'Ulûm Al-Qur'ân from Indonesian scientists in this area of technological know-how skilled pretty great traits and there had been increasingly more, with the invention of 21 works which were extra than preceding studies and had no longer been used because the item of studies. those works are a actual contribution from Indonesian scientists in writing the work 'Ulûm Al-Qur'ân, and then it is hoped that those works can end up a source of reference inside the route 'Ulûm Al-Qur'ân after which serve as a supply of reference inside the bibliography. for other next works, parallel to the work of different students of the Islamic international.